Pengaruh Personal Branding, Keragaman Produk, Dan Promosi Terhadap Minat Beli Di Isna Store Kec. Ngoro Kab. Mojokerto - Dwi Indah Kinanti; Rois Arifin; M. Tody Arsyianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Isna Store is a relatively new department store located in Dsn. Kecapangan Ds. Ngoro Rt.10 Rw.03 Kec. Ngoro Kab. Mojokerto. Previously, the Isna Store was only a small shop that was not well known and even had a few enthusiasts, but as people's interest in making purchases at Isna Store increased, this business grew and the number of buyers increased. The type of research used is explanatory research. With a quantitative research approach . The population of this research is 400 of the average consumers of Isna Store every month. In determining the sample of this study using the slovin formula, so that as many as 80 respondents were obtained who were targeted for Isna Store consumers who were met by researchers by chance when making purchases. From the results of the F test it was stated that personal branding (X1), product diversity (X2), and promotion (X3) had an effect on buying interest (Y) at Isna Store. Based on the results of the t test, it is known that personal branding (X1) has a partial effect on purchase intention (Y), product diversity (X2) has no partial effect on purchase intention (Y), and promotion (X3) has a partial effect on purchase intention (Y ). Based on the research that has been done, Isna Store must pay attention to the benefits and effects of personal branding, product variety, and promotions in order to increase consumer buying interest more than before. And for further research, it is recommended to add research variables so that it is better known what factors influence consumer interest in shopping at the Isna Store. Keywords: Personal Branding, Product Diversity, and Promotion